Analisis Efektivitas Daya Tampung Embung Taman Firdaus Universitas Sriwijaya - Rivadavia Raykaru Putra; Dinar D.A. Putranto; Putri Kusuma Wardani (Syntax Literate, 2023)
Floods occur due to reduced water catchment areas due to increased land use, both for settlements and economic activities. The purpose of this research is to analyze the storage capacity of the embankment. The Firdaus Taman Firdaus Reservoir of Sriwijaya University (UNSRI) is located in the Ogan Ilir district and is useful as a place for rainwater storage and flood control. Embung has many benefits to meet the water needs of UNSRI. The UNSRI reservoir has an area of ​​24 hectares, the west reservoir is 8 m from the bottom and 50 m long. Results of data analysis, the volume of the reservoir with a depth of 5 m with an area of ​​pond 1 covering an area of ​​423804.79 m2 can accommodate water with a storage volume capacity of 2119023.95 m3. The results of testing the average water content in the original soil (w) = 87.38 %. The test results for the average soil specific gravity (Gs) are 2.19. The results of the Atterberg limit test, the liquid limit value in soil (LL) = 57.00 %, the plastic limit in soil (PL) = 48.37 %, and the plasticity index in soil (IP) = 8.63 %. Based on the AASTHO classification, the soil in the UNSRI Firdaus Taman Embung belongs to group A-2-5, as silt or loamy gravel and sand. Meanwhile, based on the USCS classification, it is classified as Silts and Clays (CH). The results of the permeability test are the permeability value (K) = 3.034191 x 10-5 cm/s, which is low permeability.